Flipped Classroom: A Digital Revolution Learning Strategy for Curriculum 2013 - Mardhiah Masril; Billy Hendrik; Harry Theozard Fikri; Firdaus Firdaus; Hasri Awal (Universitas Muhammadiyah Enrekang, 2022)
This study aims to analyze the suitability of flipped classrooms, a 21st-century learning method, with the curriculum implemented in Indonesia in 2013. The methodology used in this research is qualitative, using a literature study as the data collection method. Data collection was conducted with the main object of surveying relevant literature. Data analysis in this research is descriptive qualitative. The results of this study show that flipped classroom learning follows the principles of learning in the 2013 curriculum. Evidenced by the implementation process, which is more student-centered. In addition, activities such as observing, questioning, gathering information, associating, analyzing, and communicating can be implemented in a technology-enhanced classroom to develop skills appropriate for the 21st century.